2015
DOI: 10.3892/ijo.2015.2936
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid inhibits the invasion of MDA-MB-231 breast cancer cells through upregulation of cytokeratin-1

Abstract: Abstract. Docosahexaenoic acid (DHa), the main member of the omega-3 essential fatty acid family, has been shown to reduce the invasion of the triple-negative breast cancer cell line MDa-MB-231, but the mechanism involved remains unclear. In the present study, a proteomic approach was used to define changes in protein expression induced by DHa. Proteins from crude membrane preparations of MDa-MB-231 cells treated with 100 µM DHa were separated by two-dimensional electrophoresis (2-De) and differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…GRN, CD5L, ENO1, CHL1, CRISP3, VASN, and TNIK promote the invasive ability of tumor cells (Aran et al, 2018;Bhandari et al, 2019;Buhusi et al, 2003;Chon et al, 2016;Song et al, 2014;Voshtani et al, 2019;Wang et al, 2019). By contrast, SEMA4B, KRT1, KRT9, FBLN1, and PTGDS are involved in the anti-invasive activity of tumor cells (Blanckaert et al, 2015;Jian et al, 2015;Marano et al, 2018;Zhang et al, 2018). MMP2 plays an important role in trophoblast invasion and is generally thought to be downregulated in PE (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…GRN, CD5L, ENO1, CHL1, CRISP3, VASN, and TNIK promote the invasive ability of tumor cells (Aran et al, 2018;Bhandari et al, 2019;Buhusi et al, 2003;Chon et al, 2016;Song et al, 2014;Voshtani et al, 2019;Wang et al, 2019). By contrast, SEMA4B, KRT1, KRT9, FBLN1, and PTGDS are involved in the anti-invasive activity of tumor cells (Blanckaert et al, 2015;Jian et al, 2015;Marano et al, 2018;Zhang et al, 2018). MMP2 plays an important role in trophoblast invasion and is generally thought to be downregulated in PE (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary unsaturated fatty acids, particularly DHA, are considered to serve an important role in reducing the risk of developing BC ( 4 ). Certain evidence has demonstrated that DHA oil is beneficial for inhibiting mammary gland carcinogenesis ( 5 – 10 ). The mechanisms of DHA oil on the inhibition of tumor proliferation and the promotion of apoptosis are complex ( 5 – 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain evidence has demonstrated that DHA oil is beneficial for inhibiting mammary gland carcinogenesis ( 5 – 10 ). The mechanisms of DHA oil on the inhibition of tumor proliferation and the promotion of apoptosis are complex ( 5 – 10 ). Among the numerous key factors, oxidative stress serves an important role in the initiation, promotion, progression and apoptosis of BC by interfering with the intracellular signal transduction pathways, and inducing DNA damage ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activating the EMT and progressing through the metastatic process is a key determinant of BC prognosis as the median survival rate for metastatic TNBC is ~10–13 mo ( 5 ). In addition to proliferation, DHA was shown to inhibit migration ( 44 , 49 , 51 , 52 ) and invasion ( 41 , 44 , 50 ) of TNBC in culture. Mouse experiments using the tail vein injection model in Fat-1 mice, which produce higher amounts of endogenous ω-3 essential fatty acids, also suggested a potential anti-metastatic effect ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with DHA (100 μM for 24 h) also decreased invasion of MDA-MB-231 cells in Boyden chamber assays by 60% compared to control cells ( 50 ). These effects were abrogated upon co-treatment with siRNA against keratin, type II cytoskeletal 1 (KRT1), which was significantly upregulated upon treatment with DHA alone.…”
Section: Fish Oil and Tnbc: Reviewmentioning
confidence: 97%